The upper Neretva River discontinuum: gradients of taxonomic and functional diversity of benthic invertebrates in a wild Balkan river - Edurne Estévez; Davina Dietrich; Simone Sahler; Fabian Vassanelli; Sara Widera; Jan Martini; Wolfgang Wanek; Gabriel Singer (Natura Sloveniae)
Free-flowing rivers are highly valuable to understand the taxonomic and functional community structure of organisms that inhabit fluvial ecosystems. We investigated patterns of macroinvertebrate community composition and food web structure using stable isotopes (δ13C and δ15N), including potential environmental drivers, over a free-flowing river continuum in the upper course of the Neretva River in Bosnia and Herzegovina. Results showed a high taxonomic diversity, a high percentage of EPT taxa (Ephemeroptera, Plecoptera, Trichoptera), and a slightly heterotrophic ecosystem (average allochthonous assimilation = 54%). The taxonomic composition differed prominently between a tributary located upstream and the mainstem. However, we also found notable species turnover between the upper (headwater and midsection) reaches and the downstream reaches of the mainstem. Macroinvertebrate abundance and the percentage of EPT peaked downstream while midsection reaches showed the highest taxonomic richness and diversity and allochthonous assimilation. Most of the functional metrics (maximum and average trophic position and isotopic richness and evenness) showed pronounced discontinuities in their spatial patterns, which did not follow the predictions of the River Continuum Concept. These results highlight the uniqueness of this section of the Neretva, where natural discontinuities structure macroinvertebrate communities in ways and by mechanisms not captured by smooth ecological concepts.